Learn Linux in 5 days (Manning Publications, 2022)
In this course, you'll learn how to install a web server, how to install a database server, how to create database users, and how to configure WordPress. Before you know it, you'll have a fully functioning blog on your hands. This is a great way to put your new-found Linux skills to good use. First, you'll learn what software is required for WordPress to run on a Linux system. Next, you'll be given the exact commands to type that install all the required software and WordPress. If you want to learn the ins-and-outs of the Linux Operating System, join this course today. You will be guided step by step using a logical and systematic approach. As new concepts, commands, or jargon are encountered they are explained in plain language, making it easy for anyone to understand.